The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14074249
|View full text |Cite
|
Sign up to set email alerts
|

Wind Energy Assessments in the Northern Romanian Coastal Environment Based on 20 Years of Data Coming from Different Sources

Abstract: Based on the fact that the wind speed tends to increase as we go from onshore to offshore, the aim of this work is to perform an analysis of a Romanian coastal sector located near the Danube Delta. Over the course of 20 years (2001–2020), in situ observations and reanalysis data (ERA5 and MERRA-2) of the local wind conditions were evaluated from a meteorological and renewable point of view. This evaluation includes two onshore sites (Galati and Tulcea), one site located near the shoreline (Sulina) and also two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…As a consequence, several research papers focused on the wind energy from this region were published; this is the case for Rusu [14] or Raileanu [29] where an offshore wind farm was proposed to partially cover the energy demand of the Constanta harbor (Romania). In Yildirir et al [30], the wind resources from the onshore and shoreline area were discussed by making a direct comparison between ERA5 and in situ measurements. According to these results, it was found that for the average values, ERA5 underestimates the onshore wind conditions located below 9 m/s, while as we go near the shoreline, a reverse pattern is noticed (close to Sulina site).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, several research papers focused on the wind energy from this region were published; this is the case for Rusu [14] or Raileanu [29] where an offshore wind farm was proposed to partially cover the energy demand of the Constanta harbor (Romania). In Yildirir et al [30], the wind resources from the onshore and shoreline area were discussed by making a direct comparison between ERA5 and in situ measurements. According to these results, it was found that for the average values, ERA5 underestimates the onshore wind conditions located below 9 m/s, while as we go near the shoreline, a reverse pattern is noticed (close to Sulina site).…”
Section: Discussionmentioning
confidence: 99%
“…At this moment, the geopolitical situation in the Black Sea is not a stable one, with this aspect being reflected in the cost of electricity and due to the fact that some countries from this region (e.g., Romania) are depending on the electricity imports being forced in some cases to reactivate some coal power plants that were closed until now [30]. From all the countries located in the Black Sea area, the best chances to develop an offshore wind project are related to Bulgaria and Romania that may benefit from the initiatives proposed under the European Green Deal [44].…”
Section: Discussionmentioning
confidence: 99%
“…Romania is a feasible candidate for floating wind implementation [83,84]. However, it lacks electrical infrastructures in the sea areas, which will make it necessary to implement floating wind Power-to-X technology that will do the job of transforming the produced electrical power mainly into hydrogen or compressed air, before accordingly transporting it through ships or other means to offshore or onshore customers.…”
Section: References Regarding the Global Floating Wind Situation With...mentioning
confidence: 99%
“…where D 0 is the rotor diameter (in m), and X 01 is the distance between two wind turbines. This type of mathematically described model is further used in the respective software, WAsP [40,41]. The results are further presented graphically in the form of maps, making the change and the role of the effect under discussion more understandable.…”
Section: Waspmentioning
confidence: 99%